The Use and Duration of Preintubation Respiratory Support Is Associated With Increased Mortality in Immunocompromised Children With Acute Respiratory Failure*. Issue 7 (14th March 2022) - Lindell, Robert B.; Fitzgerald, Julie C.; Rowan, Courtney M.; Flori, Heidi R.; Di Nardo, Matteo; Napolitano, Natalie; Traynor, Danielle M.; Lenz, Kyle B.; Emeriaud, Guillaume; Jeyapalan, Asumthia; Nishisaki, Akira; ,
Abstract : OBJECTIVES: To determine the association between preintubation respiratory support and outcomes in patients with acute respiratory failure and to determine the impact of immunocompromised (IC) diagnoses on outcomes after adjustment for illness severity. DESIGN: Retrospective multicenter cohort study. SETTING: Eighty-two centers in the Virtual Pediatric Systems database. PATIENTS: Children 1 month to 17 years old intubated in the PICU who received invasive mechanical ventilation (IMV) for greater than or equal to 24 hours. INTERVENTIONS: None. MEASUREMENTS AND MAIN RESULTS: High-flow nasal cannula (HFNC) or noninvasive positive-pressure ventilation (NIPPV) or both were used prior to intubation in 1, 825 (34%) of 5, 348 PICU intubations across 82 centers. When stratified by IC status, 50% of patients had no IC diagnosis, whereas 41% were IC without prior hematopoietic cell transplant (HCT) and 9% had prior HCT. Compared with patients intubated without prior support, preintubation exposure to HFNC (adjusted odds ratio [aOR], 1.33; 95% CI, 1.10–1.62) or NIPPV (aOR, 1.44; 95% CI, 1.20–1.74) was associated with increased odds of PICU mortality. Within subgroups of IC status, preintubation respiratory support was associated with increased odds of PICU mortality in IC patients (HFNC: aOR, 1.50; 95% CI, 1.11–2.03; NIPPV: aOR, 1.76; 95% CI, 1.31–2.35) and HCT patients (HFNC: aOR, 1.75; 95% CI, 1.07–2.86; NIPPV: aOR, 1.85; 95% CI, 1.12–3.02) compared with IC/HCT patients intubated without prior respiratory support. Preintubation exposure to HFNC/NIPPV was not associated with mortality in patients without an IC diagnosis. Duration of HFNC/NIPPV greater than 6 hours was associated with increased mortality in IC HCT patients (HFNC: aOR, 2.41; 95% CI, 1.05–5.55; NIPPV: aOR, 2.53; 95% CI, 1.04–6.15) and patients compared HCT patients with less than 6-hour HFNC/NIPPV exposure. After adjustment for patient and center characteristics, both preintubation HFNC/NIPPV use (median, 15%; range, 0–63%) and PICU mortality varied by center. CONCLUSIONS: In IC pediatric patients, preintubation exposure to HFNC and/or NIPPV is associated with increased odds of PICU mortality, independent of illness severity. Longer duration of exposure to HFNC/NIPPV prior to IMV is associated with increased mortality in HCT patients.